Implications for a Stem Cell Regenerative Medicine Based Approach to Human Intervertebral Disk Degeneration - Kraus, Petra; Lufkin, Thomas (Frontiers in Cell and Developmental Biology, 2017)
The human body develops from a single cell, the zygote, the product of the maternal oocyte and the paternal spermatozoon. That 1-cell zygote embryo will divide and eventually grow into an adult human which is comprised of ~3.7 × 1013 cells. The tens of trillions of cells in the adult human can be classified into approximately 200 different highly specialized cell types that make up all of the different tissues and organs of the human body. Regenerative medicine aims to replace or restore dysfunctional cells, tissues and organs with fully functional ones. One area receiving attention is regeneration of the intervertebral discs (IVDs), which are located between the vertebrae and function to give flexibility and support load to the spine. Degenerated discs are a major cause of lower back pain. Different stem cell based regenerative medicine approaches to cure disc degeneration are now available, including using autologous mesenchymal stem cells (MSCs), induced pluripotent stem cells (iPSCs) and even attempts at direct transdifferentiation of somatic cells. Here we discuss some of the recent advances, successes, drawbacks, and the failures of the above-mentioned approaches.